Sung-Hee Jwa. A General Theory of Economic Development—Towards a Capitalist Manifesto. Cheltenham, UK: Edward Elgar Publishing. 2017. x+215 pages. Price UK £ 67.50 (Hardback). (The Pakistan Development Review, 2017)
A General Theory of Economic Development is yet another attempt to demystify the underlining causes of underdevelopment and economic stagnation, and to offer a theory of economic development, which has proved to be an elusive quest for most of the world economies. Apart from a handful of developed economies, most of the other world economies are merely also-rans in the quest for economic development. In fact, even those economies that have been growing at respectable rates over the last decade or two, such as China, cannot yet claim to be developed countries. It is in this backdrop that Sung-Hee Jwa has written this book that offers a theory of economic development. It is a daring attempt as it departs from the standard growth models and development theories and challenges the conventional wisdom. The theory put forth in the book, according to the author, is not only applicable to the developing, or underdeveloped, countries, but is equally applicable to the developed countries, hence meriting the word ‘general’ in the title.